2019
DOI: 10.1016/j.ogla.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Increases Intraocular Pressure in Nonhuman Primates

Abstract: Purpose: To quantify intraocular pressure (IOP) change and time course during stressful activity Study Design: Experimental Study Subjects: Three nonhuman primates (NHPs) Methods: Bilateral IOP and aortic blood pressure (BP) were recorded continuously, then averaged for periods of 8-30 seconds before, during, and after a common anesthetic induction procedure (cage squeeze followed by intramuscular injection). Experiments were repeated four times in each NHP. Main Outcome Measures: IOP, BP, and heart rate (HR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…Results show that changes in IOP with injectable and inhalant anesthesia relative to precontact baseline are generally small, which bodes well for clinical and animal research activities that rely on postanesthesia IOP measurements. Both this study and a recent study from our group show that acute stress associated with human contact significantly elevates IOP, MAP, and HR in NHPs, demonstrating the importance of measuring IOP using telemetry that doesn't require human contact 1. Anesthesia did lower IOP significantly when compared to IOP measured when the NHPs are in contact with staff (mean decrease of 5.4 mm Hg), but this is likely to be due to the relaxation of the animals from a stressful state and not the pharmacologic effects of the anesthesia itself, as postulated in prior NHP and human studies 1,15.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Results show that changes in IOP with injectable and inhalant anesthesia relative to precontact baseline are generally small, which bodes well for clinical and animal research activities that rely on postanesthesia IOP measurements. Both this study and a recent study from our group show that acute stress associated with human contact significantly elevates IOP, MAP, and HR in NHPs, demonstrating the importance of measuring IOP using telemetry that doesn't require human contact 1. Anesthesia did lower IOP significantly when compared to IOP measured when the NHPs are in contact with staff (mean decrease of 5.4 mm Hg), but this is likely to be due to the relaxation of the animals from a stressful state and not the pharmacologic effects of the anesthesia itself, as postulated in prior NHP and human studies 1,15.…”
Section: Discussionsupporting
confidence: 60%
“…Both this study and a recent study from our group show that acute stress associated with human contact significantly elevates IOP, MAP, and HR in NHPs, demonstrating the importance of measuring IOP using telemetry that doesn't require human contact 1. Anesthesia did lower IOP significantly when compared to IOP measured when the NHPs are in contact with staff (mean decrease of 5.4 mm Hg), but this is likely to be due to the relaxation of the animals from a stressful state and not the pharmacologic effects of the anesthesia itself, as postulated in prior NHP and human studies 1,15. Previous studies have shown that changes in IOP can be modulated through relaxation of the extraocular muscles, which could be the mechanism through which anesthesia acutely lowers IOP when the subject is stressed and IOP is acutely elevated as a result 25.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations